Study about Wind Energy Map of Arabian Gulf: Advantages and Challenges - Khaled Al-Salem; S. Neelamani; Waleed Al-Nassar (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 9, 2023)
The main objectives of this chapter are to come up with wind energy map of Arabian Gulf based on statistical analysis of long term data. Sustainable development is possible by use of sustainable energy and by ensuring access to affordable, reliable, sustainable, and modern energy for citizens. Wind power is the conversion of wind energy into a useful form of energy, such as using wind turbines to make electricity, windmills for mechanical power, wind pumps for water pumping or drainage, or sails to propel ships. This paper is on the wind energy resource availability over Arabian Gulf waters, covering 2300 grid points. The data available with Coastal Information System data base at Kuwait Institute for Scientific Research, Kuwait, from 1979 to 2015 is used. Electricity consumption in GCC countries increased rapidly during the last three decades not only in absolute terms, but also in terms of its share in total energy demand. From the data sources, the probability density and power density were determined. The wind power density was assessed by fitting the Weibull probability density function to the wind speed data. The investigation is conducted at elevations of 10, 30, and 50 meters. The Weibull shape parameter k varies from 2.5 to 3 at the north and central of the Arabian Gulf. The annual mean wind power density over Arabian Gulf Waters is the highest in the central region of the Gulf. The power density at 10 m, 30 m and 50 m hub height varies be-tween 200 to 300 w/m2, 200 to 300 w/m2 and more than 300 w/m2 respectively. Since the Arabian Gulf’s core region falls inside the Wind Energy Resource Atlas of the United States’ Class 2 category, it is appealing to develop large-scale wind power generation there at elevations of 30 or 50 meters. Since air conditioning systems utilize a lot of power in the summer, the wind power density is particularly appealing in the center region of the Arabian Gulf (Saudi Arabia, Bahrain, and Qatar).